Accuracy of Femoral Head and Neck Excision via a Craniolateral Approach or a Ventral Approach - Winders, Callie L. Blackford; Vaughn, William L.; Birdwhistell, Kate E.; Holsworth, Ian G.; Franklin, Samuel P. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives This study aimed to compare the completeness of femoral head and neck removal via a craniolateral approach or a ventral approach when femoral head and neck excision (FHNE) is performed by a novice veterinarian.Methods FHNE was performed on both femurs of 10 canine cadavers with each femur randomized by a coin toss to FHNE via the craniolateral or ventral approach. Computed tomography (CT) of the femurs was performed prior to and following FHNE. The volume of bone that should have been removed with an ideal FHNE, the percentage of this volume that remained following FHNE, time to complete the procedure and the number of technical errors were compared between the two groups.Results No significant difference (p = 0.88) was found in the volume of bone that should have been removed with an ideal ostectomy when using the two approaches (craniolateral 3,814.7 ± 409.4 mm3; ventral 3,806.2 ± 479.4 mm3), mean excess residual femoral neck (craniolateral 6.0 ± 9.6%; ventral 4.8 ± 6.8%), mean duration of the procedure (craniolateral 19.3 ± 5.4 minutes; ventral 23.7 ± 5.6 minutes) or number of technical errors (craniolateral 0/10; ventral 1/10) between the craniolateral and ventral approach groups.Clinical Relevance The completeness of bone removal was not significantly different when FHNE was performed by a novice veterinarian via a craniolateral or ventral approach.
Keywords: femoral head and neck excision; femoral head ostectomy; cadaver; dog